Key policy issues in long-term care - Brodsky, Jenny; Habib, Jack; Hirschfeld, Miriam (World Health Organization collection on long-term care., 2003)
Demographic and epidemiological transitions will result in dramatic changes in the health needs of the world's populations. Everywhere, there is a steep increase in the need for long-term care (LTC). These trends reflect two interrelated processes. One is the growth in factors that increase the prevalence of long-term disability in the population. The second is the change in the capacity of the informal support system to address these needs. Both of these processes enhance the urgency for public policies to address the consequences of these changes. The growing need for LTC policies is general.